ANALISIS SEKTOR UNGGULAN DAN SPESIALISASI REGIONAL KOTA BANDAR LAMPUNG (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2019)
Economic growth is one of the benchmarks that can be used to increase the development of an area of various economic sectors which indirectly illustrates the level of economic change. Regional development must be in accordance with the conditions of the potential and aspirations of people who grow and develop. If the implementation of regional development priorities is not in accordance with the potential of each region, the utilization of available resources will be less than optimal. This study aims to identify leading sectors and regional specializations in Bandar Lampung City. The data used in this study are secondary data from 2008-2012 sourced from the Provincial BPS and City BPS. The analysis model used is LQ Analysis, Klassen Typology and Regional Specialization Analysis. The results showed that there were seven basic sectors in the Bandar Lampung City economy including the manufacturing sector, the electricity, gas and water supply sector, the construction sector, the trade, hotel and restaurant sector, the transportation / communication sector, the banking sector and other financial institutions, and service sector. While the Klassen Typology analysis results, there is one leading sector in the economy of Bandar Lampung City, namely the manufacturing sector. However, there is no regional specialization in Bandar Lampung City